2003
DOI: 10.1002/cncr.11807
|View full text |Cite
|
Sign up to set email alerts
|

Vinblastine, bleomycin, and methotrexate chemotherapy plus irradiation for patients with early‐stage, favorable Hodgkin lymphoma

Abstract: BACKGROUNDThe acknowledged effectiveness of vinblastine, bleomycin, and methotrexate (VBM) chemotherapy in patients with early‐stage Hodgkin lymphoma has been associated with conflicting toxicity reports.METHODSOne hundred forty‐three patients were evaluated clinically and had favorable Stage IA or IIA Hodgkin lymphoma. Ninety‐three patients were treated with the standard VBM schedule combined with extended‐field radiotherapy (EF‐RT), leaving the choice of the therapeutic sequence free. Fifty subsequent patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…The global prognosis for patients with LPHL is excellent, as demonstrated in previous studies, with an OS rate of ≈95% and a PFS rate between 85% and 94% 15–18. Our study confirmed these results, with a 100% OS rate at a median follow‐up of 4 years.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The global prognosis for patients with LPHL is excellent, as demonstrated in previous studies, with an OS rate of ≈95% and a PFS rate between 85% and 94% 15–18. Our study confirmed these results, with a 100% OS rate at a median follow‐up of 4 years.…”
Section: Discussionsupporting
confidence: 90%
“…The prognosis is favorable with an indolent course of disease, and the rare patient deaths are related to secondary (treatment‐related) malignancies or transformation to aggressive B‐cell lymphoma9–14 or classic Hodgkin lymphoma (HL). In the past, patients with LPHL often have been treated with chemotherapy and radiotherapy according to standard, classic HL protocols 15–17. Patients with early‐stage disease who were treated with radiotherapy alone usually received extended‐field radiation,18–20 chemotherapy alone,21 or, more recently in adults, monoclonal antibody therapy with rituximab 21–23.…”
mentioning
confidence: 99%
“…To reach their conclusions, the experts extensively analyzed large randomized clinical trials conducted in the last 15 years, whose results have been published as full papers [13][14][15][16][17][18][19][20][21] or as abstracts. [22][23][24][25] A number of cohort studies, 3,26,27 and the results of Cochrane analysis on chemotherapy, RT and combined modality for HL 28 have also been considered. For decades, RT has been the standard of care for patients with early stage HL.…”
Section: First-line Therapy For Early Stage Diseasementioning
confidence: 99%
“…Patients with a low-risk were treated with a VBM (vinblastine, bleomycin, methotrexate)-based CC plus involved-field radiotherapy (IF-RT). 9 Patients with an intermediate-risk were treated with four courses of an adriamycin-including regimen, that is, ABVD 10 Patients with HL who did not respond to an induction CC, whether they had progressive, stable or only minimally responsive disease were considered to have primary refractory HL. Out of the 1078 HL patients, 82 cases failed (7.6%).…”
Section: Patientsmentioning
confidence: 99%